2020
DOI: 10.1111/sltb.12686
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the scope and structure of suicide capability

Abstract: ObjectiveRecent theories of suicide suggest that a construct called “capability for suicide” facilitates the progression from suicidal thoughts to attempts. Various measures of capability have been developed to assess different parts of the construct, but studies report inconsistent findings regarding reliability, validity, and structure. The present study pooled items from multiple measures to identify distinct, reliable, and valid domains of suicide capability.MethodWe administered items from several suicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 47 publications
3
37
0
1
Order By: Relevance
“…As previously described in Shahnaz et al (2020), participants reported a mean age of 35.6 years (SD = 10.59). The majority of participants were female (62.3%), White (73.1%), and heterosexual (82.9%).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…As previously described in Shahnaz et al (2020), participants reported a mean age of 35.6 years (SD = 10.59). The majority of participants were female (62.3%), White (73.1%), and heterosexual (82.9%).…”
Section: Resultsmentioning
confidence: 73%
“…Regarding suicide history, 203 (52.5%) reported no lifetime history of suicidal thoughts or behaviors (nonsuicidal participants), 114 (29.5%) reported a lifetime history of suicide ideation but no history of suicide attempts (ideators), and 70 (18.1%) reported a lifetime history of suicide attempts (attempters). Data regarding descriptive information about suicide attempts, including types of suicide attempts endorsed, can be found in Table 1 in Shahnaz et al (2020). During the peer review process, a reviewer noted that both gender and sexual orientation are often associated with ED features and suicide ideation and attempts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the perceived 'painlessness', the identified sociocultural perceptions towards charcoal-burning suicide in this study can be better understood in the construct of 'capability for suicide'-fearlessness about death, practical capability, and pain tolerance-which researchers propose to facilitate the progression from suicidal ideations to attempts [19]. Up to 77.6% of respondents who contemplated charcoal-burning suicide perceived that this method leaves behind an intact body after death, whereas only 49.8% of those not contemplating charcoal-burning suicide had this perception.…”
Section: Plos Onementioning
confidence: 96%
“…We further stress that researchers must be careful regarding their measurement of key constructs associated with suicide (Shahnaz et al, 2020). Large-scale mortality databases are often believed to include objective indicators of suicide, but these databases are typically created from death certificates.…”
Section: Goal 15mentioning
confidence: 99%